The Major Qualitative Characteristics of Olive (Olea europaea L.) Cultivated in Southwest China - Cheng, Zizhang; Zhan, Mingming; Yang, Zeshen; Zumstein, Kristina; Chen, Huaping; Huang, Qianming (Frontiers in Plant Science, 2017)
Olive trees, originated from Mediterranean, have been cultivated in China for decades and show great adaption to local environment. However, research on this topic is limited. In this study, the major qualitative characteristics and changes of olive grown in southwest China were investigated. The results showed that oil accumulated during fruit development and reached its maximum value when fruit had fully ripened. Phenolic and flavonoid contents increase rapidly in the early growth stage (0-90 DAFB) and then begin to decrease as fruit ripens. Compared with olive from the Mediterranean, olive from China has special characteristics: higher moisture content in the fruit combined with lower percentages of unsaturated fatty acids and oil content. This is due to southwest China’s climate which is wetter and cooler compared to the Mediterranean. Our study suggests that southwest China’s higher annual rainfall might contribute to higher fruit moisture content while its low temperatures would be conducive to higher unsaturated fatty acid levels in the fruit.